O uso da escala de desenvolvimento motor em crianças com Transtorno do Espectro Autista (TEA) - SANTOS, Lucas Justiniano Alves dos (2022)
Children with Autism Spectrum Disorder (ASD) have motor development delays and assessing these delays is still seen as a challenge in psychomotor assessment, mainly to specifically identify areas in which the child is less developed. The aim of this study was to assess whether psychomotor interventions have any effect on motor development in children with ASD. The present study is a case study, in a descriptive way, which sought to analyze and compare the child's motor profile through the motor development scale (MDS) before and after 20 psychomotricity sessions. For the evaluated child, his general motor age was -26 months in the first test and -23 months in the second test, remaining at a negative age (IN), but reducing his NI by 3 months, increasing his general motor age (IMG ) at 8 months and his overall motor quotient (QMG) at 3 months in the second test compared to the first. Its psychomotor components that suffered the main delays were its body schema and spatial orientation. It was possible to reach the result of delay in their motor development through the use of EDM.